Medical marijuana use for pediatric oncology patients: single institution experience. (4th July 2019) - Ofir, Ruth; Bar-Sela, Gil; Weyl Ben-Arush, Myriam; Postovsky, Sergey
Abstract: Medical marijuana (MM) is widespread in many medical fields, including oncology, with limited use in pediatric oncology where research is scarce and often shows conflicting results. This research focuses on alleviating side effects of anticancer treatment as an integral part of supportive and palliative care of children with cancer. We report our experience with MM treatment in 50 children, adolescents, and young adults with different types of cancer during 2010–2017. The main indications for prescriptions were nausea and vomiting, decreased mood, disturbed sleep, and pain. The medication was supplied to 30 patients via oil drops (60%) and 11 via smoking (22%), followed by vaporization, capsules, or combinations of various routes. Positive effects were reported by verbal children and parents in 80% of cases. MM was generally well tolerated with few patients reporting toxicity, with the most common adverse reactions being burning in the throat and anxiety attacks in subjects who chose to smoke the product. We conclude that MM may serve as a potentially useful complementary therapy to conventional supportive treatment of children suffering from cancer at the end of life. Further research is needed on the safety and efficacy and the consequences of prolonged use in pediatric populations.